Impact of Career Development and Work-Life Balance on Job Satisfaction Mediated by Work Engagement Among Nurses in Kubu Raya - Liau Ie Hau; Hasanudin Hasanudin; Ikram Yakin; Arman Jaya (Digital Innovation : International Journal of Management, 2025)
With an emphasis on work engagement as a mediating variable, this study intends to investigate the effects of career development and work-life balance on job satisfaction among nurses in Kubu Raya, West Kalimantan. Using a quantitative methodology, structured questionnaires were used to gather data from 223 nurses, and SmartPLS software assisted in the analysis of the data using Structural Equation Modeling (SEM). Purposive sampling was used in the study, and one of the selection factors was the length of employment. The results show that work-life balance also has a positive and significant impact on work engagement, and career growth has a positive and large impact on work engagement. Furthermore, work-life balance and career advancement both directly, favorably, and significantly impact job satisfaction. Job satisfaction has been demonstrated to be favorably and significantly influenced by work engagement, which acts as a meaningful mediator. Furthermore, through work engagement, career development and work-life balance both have a positive and statistically significant mediation effect on job satisfaction.